The shepherd boy and the wolf - N/A (Selongor : Mind to mind)
A shepherd boy lied several times by shouting (3z(BWolf!(3y (Bto trick villagers for fun. When a real wolf came, no one believed him, and the sheep were lost. Moral: Don$1 (Bt lie$1 (Bpeople won$1 (Bt trust you when you really need help.s
Keywords: English